A historico-theological study of Pentecostalism as a phenomenon within a South African community - Pillay, Gerald J (Rhodes University, Faculty of Divinity, Department of Divinity, 1985)
Preface: An attempt is made in this thesis to document the history of Pentecostalism among Indians in South Africa and to study and evaluate its religious character and main theological tenets. Obviously the peculiar socio-political situation of the Indians in South Africa has influenced the character of Indian Pentecostalism, which has in turn been able to address itself to the critical, cultural and religious disjunctions within this community. Hence an investigation of the dynamic tensions that obtain between crises in the Indian community and Pentecostalism will not only clarify the course of its history but will also explain its theological emphases. However, several studies on Pentecostalism in other communities have concentrated on the sociological dimension almost exclusively and many have even concluded that Pentecostalism is the spontaneous result of psychosocial; economic or cultural upheavals . This kind of reductionism has been largely the result of the uncritical use of 'functional-type' theories postulated by sociologists of religion. Indian Pentecostalism, while it has to be examined within the complex context of the South African community, cannot as we shall show, be adequately explained by any of the prevailing 'functional-type' theories because these theories reduce religion to a sociological function. Since the functional theory has the effect of limiting the perspective on religion to such an extent that the basis of religion, that is, the relation between the individual and faith, is either belittled or ignored, it has been jettisoned in this thesis for an approach free of any deliberately formulated 'theoretical framework'. However, it is necessary to critically examine some of the more popular 'functional-type' theories and the way they have been applied to the study of the Pentecostal movement here and elsewhere, so that by exposing the shortcomings of their application and the contradictions inherent in their assumptions, the approach adopted in this thesis could be clarified.
Keywords: Pentecostalism -- South Africa; Pentecostal churches -- South Africa